The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/fsn3.551
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting of powdered pineapple rind as an organic supplement of composted sawdust for Pleurotus ostreatus mushroom cultivation

Abstract: Pineapple rind is a by‐product of the pineapple processing industry and contains nutrients and other compounds which must be utilized as a bioresource for socio‐economic benefits while preventing the potential problems of improper agroindustrial biomass disposal methods. Pleurotus ostreatus is an edible oyster mushroom with medicinal properties and can be cultivated on various agroindustrial biomass, including sawdust containing supplements. Pineapple rind was powdered and used as a supplement of composted saw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
4
4
3
Order By: Relevance
“…Paddy straw has been preferred as the substrate for its financial efficiency and abundance. The nutritional composition, as obtained through proximate analysis, of the mushroom in the current study is compatible with what has been reported by other previous studies who used costlier substrates like pineapple rind (Narh et al, 2018), banana leaves, groundnut shell, cassava and yam peel and sawdust, etc. (Peter et al, 2019) (discussed in details in Section 3.2).…”
Section: Cultivation Of P Ostreatussupporting
confidence: 92%
See 2 more Smart Citations
“…Paddy straw has been preferred as the substrate for its financial efficiency and abundance. The nutritional composition, as obtained through proximate analysis, of the mushroom in the current study is compatible with what has been reported by other previous studies who used costlier substrates like pineapple rind (Narh et al, 2018), banana leaves, groundnut shell, cassava and yam peel and sawdust, etc. (Peter et al, 2019) (discussed in details in Section 3.2).…”
Section: Cultivation Of P Ostreatussupporting
confidence: 92%
“…(Peter et al, 2019) (discussed in details in Section 3.2). Moreover, the growth time for the fruiting bodies has been found to be shorter in the current study (20 days) in comparison to other studies (34 days for pineapple rind (Narh et al, 2018)) though the productivity could have been still maintained.…”
Section: Cultivation Of P Ostreatuscontrasting
confidence: 87%
See 1 more Smart Citation
“…Depending on the origin of the waste material and on the supplement rate, authors have published different results. Narh Mensah et al [30] obtained biological efficiency of 78.8% using powdered pineapple rind supplement and 65.2% with substrate control. Pardo-Gimenez et al [31] reported biological efficiency of 100.3, 109.8, 126.9, and 127.6%, respectively, for the control substrate (without supplement) and supplemented with a defatted almond meal at a rate of 0.5%, 1.0%, and 1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Pleurotus genus has also been found applicable in the biotransformation of unsaturated terpenoid compounds [38,39]. In Africa, oyster mushrooms are grown mainly on sawdust, with the addition of rice straw [40,41].…”
Section: The Genus Pleurotusmentioning
confidence: 99%